Breves considerações sobre a lei aplicável ao contrato de seguro - Andrade Pisarra, Nuno (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
On the 1st of January 2009, a new legal regime regarding insurance contracts entered into force in Portugal. Approved by Decree-Law no. 72/2008, such regime contains, in its articles 5 to 10, new conflicts of law rules on international insurance contracts, which have replaced the former domestic conflicts rules approved by Decree-Law no. 94-B/98. Both Decree-Law no. 94-B/98 and Decree-Law no. 72/2008 aimed to transpose into Portuguese legal system the EU Directives on insurance contracts. Notwithstanding, the scope of application of articles 5 to 10 became severely affected when Rome I Regulation entered into force on December 17, 2009. Throughout the subsequent study, articles 5 to 10 of Decree-Law no. 72/2008 and the previous conflicts of law rules repealed by it, as well as the provisions established in Directives 88/357/CEE and 2002/83/CE on applicable law and those that have been introduced by Rome I Regulation shall be analyzed.
Keywords: Decree-Law no. 72/2008; Rome Convention; Rome I Regulation; Directive 88/357/CEE; Directive 2002/83/CE; Decree-Law no. 94-B/98; insurance contract; international insurance contract; applicable law; conflicts of law rules; conflicts law; risk; commitment; lois de police